2014
DOI: 10.1177/1748006x14527075
|View full text |Cite
|
Sign up to set email alerts
|

Reliability optimization through robust redundancy allocation models with choice of component type under fuzziness

Abstract: Due to the inherent uncertainty associated with various factors in the designing stage, considering uncertainty is important in system designs. In this article, a redundancy allocation problem with active strategy and choice of component type is studied where the system engineer faces with insufficient knowledge about exact values of some characteristics of components such as reliability and cost. The impreciseness is considered in terms of fuzzy numbers with triangular and trapezoidal membership functions. To… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…For convenience, let F denote the set of G satisfying constraints (9) and (11). If S is a d-MS under X, there should exist a G 2 F satisfying constraint (10). Moreover, if S is a d-MS, there exists a G 2 F such that the S is transformed from this G via equation (12)…”
Section: Minimal State For Demand Dmentioning
confidence: 99%
See 1 more Smart Citation
“…For convenience, let F denote the set of G satisfying constraints (9) and (11). If S is a d-MS under X, there should exist a G 2 F satisfying constraint (10). Moreover, if S is a d-MS, there exists a G 2 F such that the S is transformed from this G via equation (12)…”
Section: Minimal State For Demand Dmentioning
confidence: 99%
“…Therefore, a system supervisor may also wish to focus on the cost required to satisfy a reliability threshold. 7 In addition, several studies 6,[8][9][10] have shown that the redundancy strategy can maintain and promote the systemic stability. For these reasons, this article extends the previous work of Yeh and Fiondella 4 by searching for the optimal redundancy allocation of binary-state components (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Mahapatra and Mahapatra [21] considered the problem of minimizing system cost of a series system with the target of system reliability in fuzzy environment and formulated the reliability model as a fuzzy parametric geometric programming problem. Recently, Soltani and Sadjadi [22] presented a robust possibilitic programming approach and developed robust models for RAP with active strategy.…”
Section: Introductionmentioning
confidence: 99%
“…There are other models such as interval models, ellipsoid models, 22 probability box models, 23,24 evidence theory, 6,25 and fuzzy set models. [26][27][28] There are plenty of researches in RBMDO with one kind of uncertainty variables. Huang et al 29 developed an evidence theory-based reliability design optimization method in which the problem was converted into a sequential iteration process.…”
Section: Introductionmentioning
confidence: 99%